Endophytic Aspergillus hiratsukae mediated biosynthesis of silver nanoparticles and their antimicrobial and photocatalytic activities - Saied, Ebrahim; Abdel-Maksoud, Mostafa A.; Alfuraydi, Akram A.; Kiani, Bushra Hafeez; Bassyouni, Mohamed; Al-Qabandi, Osama A.; Bougafa, Fathia H. E.; Badawy, Mona Shaban E. M.; Hashem, Amr H. (Frontiers in Microbiology, 2024)
In the current study, endophytic Aspergillus hiratsukae was used for the biosynthesis of silver nanoparticles (Ag-NPs) for the first time. The characterizations were performed using X ray diffraction (XRD), Transmission electron microscopy (TEM), Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM–EDX), Dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FT-IR), and UV–Vis spectroscopy. The obtained results demonstrated the successful formation of crystalline, spherical Ag-NPs with particle diameters ranging from 16 to 31 nm. The FT-IR studied and displayed the various functional groups involved, which played a role in capping and reducing agents for Ag-NPs production. The SEM–EDX revealed that the main constituent of the AS-formed sample was primarily Ag, with a weight percentage of 64.2%. The mycosynthesized Ag-NPs were assessed for antimicrobial as well as photocatalytic activities. The antimicrobial results indicated that the synthesized Ag-NPs possess notable antibacterial efficacy against Staphylococcus aureus, Bacillus subtilis, and Escherichia coli, with minimum inhibitory concentrations (MICs) of Ag-NPs ranging from 62.5 to 250 μg/mL. Moreover, the biosynthesized Ag-NPs demonstrated weak antifungal activity against Aspergillus brasiliensis and Candida albicans, with MICs of 500 and 1,000 μg/mL, respectively. In addition, the mycosynthesized Ag-NPs exhibited photocatalytic activity toward acid black 2 (nigrosine) dye under both light and dark stimulation. Notably, After 300 min exposure to light, the nigrosine dye was degraded by 93%. In contrast, 51% degradation was observed after 300 min in darkness. In conclusion, Ag-NPs were successfully biosynthesized using endophytic A. hiratsukae and also exhibited antimicrobial and photocatalytic activities that can be used in environmental applications.